MENELUSURI JEJAK NEOLIBERAL: PLANNED OBSOLESCENCE DALAM PERUBAHAN EKONOMI GLOBAL - Christabel Benedicta Orno; Gusti Ayu Santika; Inda Ayu Makahiking (Cahaya Ilmu Bangsa, 2024)
Planned obsolescence is a practice in modern economics where manufacturers intentionally design products to become obsolete quickly, encouraging consumers to buy new products more frequently. This phenomenon has wide-ranging impacts, including increased consumption, reduced sustainability, and shifts in consumer behavior. This research analyzes the impact of planned obsolescence on the economy, environment, and technology within the context of neoliberalism theory, and seeks solutions to mitigate its negative effects. In electronic devices such as washing machines and smartphones, planned obsolescence leads to increased waste, decreased consumer trust, and economic inequality. Environmental impacts include increased electronic waste and carbon emissions, while economically, this practice fosters unsustainable growth. Effective regulation, promotion of sustainable innovation, and consumer education on the importance of choosing durable and environmentally friendly products are necessary to reduce its adverse effects.